UMPSA listed among Best Universities at MQA Awards 2025 - Naqiah, Puaad (UMPSA, 2025)
KUALA LUMPUR, 12 August 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to demonstrate its commitment to excellence in higher education as it was listed among the top five in the 2025 Quality Assurance Grand Award, top three in the Excellence Award for Higher Education Providers (HEPs) in the TVET category, as well as top five in the Excellence Award for HEPs: Internal Quality Assurance (IQA) at the recent MQA Awards 2025.